Cost-benefit analysis financial and economic appraisal using spreadsheets - Campbell, Harry F.; Brown, Richard P. C. 1951- (Routledge, 2016)
"Now in its second edition, Cost-Benefit Analysis has been updated throughout, offering readers the perfect introduction to project, program and policy appraisal using basic tools of financial and economic analysis. The key economic questions of any social cost-benefit analysis are: do the benefits of the project or policy exceed the costs, no matter how widely costs and benefits are spread, and irrespective of whether or not project impacts, such as environmental effects, are reflected in market prices? And which group or groups of individuals benefit and which bear the costs? This book addresses these questions with an emphasis on putting the theory presented in the book into practice. This second edition has several attractive features: - Readers are encouraged to develop their own skills by applying the tools and techniques of cost-benefit analysis to case studies and examples, including an analysis of a project which is developed throughout the book. - The book emphasises the use of spreadsheets which are invaluable in providing a framework for the cost-benefit analysis - A dedicated chapter provides guidance for writing up a report which summarizes the analysis which has been undertaken. - New pedagogical features, including Technical Notes and Examples, have been added as an aid to readers throughout the text. -"..
1. Aufl. u.d.T.: Campbell, Harry F.: Benefit-cost analysis
Keywords: BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Wirtschaft; Cost effectiveness; Decision making; Projektbewertung; Kosten-Nutzen-Analyse; Tabellenkalkulation; Aufgabensammlung